European immigrants in the UK before and after the 2004 enlargement: Is there a change in immigrant self-selection? - Simonetta Longhi; Magdalena Rokicka (University of Essex, Institute for Social and Economic Research (ISER), 2012)
The 2004 accession of Eastern European countries (EU8) to the European Union has generated concerns about the influx of low-skill immigrants to the Western member states (EU15). Only three countries, namely Ireland, Sweden, and the UK, did not impose restrictions to immigration from Eastern Europe. Did the elimination of barrier to immigration have an impact on the quality of immigrants arriving to the UK? Using EU15 immigrants as a control group, we find systematic differences between EU8 immigrants arrived before and after the enlargement. The elimination of barriers to immigration seems to have changed the quantity and quality of EU8 immigrants to the UK.
Keywords: F22; J30; J61; 330; EU enlargement; East-West migration; UK labour market; self-selection